Systematic Review of Olaparib in the Treatment of Recurrent Platinum Sensitive Ovarian Cancer - Chen, Qian; Li, Xiaoli; Zhang, Zhen; Wu, Tong (Frontiers in Oncology, 2022)
Objective To systematically evaluate the efficacy and safety of olaparib in the treatment of recurrent platinum-sensitive ovarian cancer. Methods The Cochrane Library, PubMed, Chinese Biomedical Literature Database, CNKI, VIP Database, Wanfang Science and Technology Database were searched for randomized controlled trials ( RCTs ) of olaparib in the treatment of recurrent platinum-sensitive ovarian cancer from the establishment of each database to January 2022. Two reviewers independently evaluated the quality of the literature, extracted the data, and cross-checked the methodological quality. Meta-analysis was performed using RevMan 5.4 software. Results A total of 7 RCTs were included, including 2406 patients, There were 1497 patients in treatment groups and 909 patients in the control group. Meta-analysis results showed that in terms of effectiveness, the overall survival time of patients in the olaparib group [HR=1.24, 95%CI(1.06, 1.45), P=0.006]; in terms of safety, for all grades of adverse events ( including nausea, fatigue, vomiting, diarrhea, abdominal pain, and headache ), [HR=1.54，95%CI(1.38，1.71), P=0.0002], for grade 3 or higher adverse events ( including nausea, fatigue, vomiting, diarrhea, abdominal pain, and headache ), [HR=2.13, 95%CI(1.61, 2.81), P=0.003], there were significant differences compared with the control group, suggesting that the risk of adverse reactions in the experimental group was higher than that in the control group. Subgroup analysis showed that only abdominal pain, headache and vomiting were not statistically significant, and other adverse reactions were statistically significant. Conclusion Based on the existing clinical evidence, olaparib in the treatment of recurrent platinum-sensitive ovarian cancer has a longer overall survival than the control group. It is an ideal regimen, but the incidence of adverse reactions is high.